The structure of schooling : readings in the sociology of education - Beattie, Irenee R.; Ford, Karly; Arum, Richard (Los Angeles : SAGE, 2021)
"This comprehensive reader examines critical topics on schools and education, and exposes students to examples of sociological research on schools with a focus on the school as community. The Structure of Schooling draws from classic and contemporary scholarship to examine current issues and diverse theoretical approaches to studying the effects of schooling on individuals and society. It covers a wide range of issues, including the development and application of social and cultural capital; the effects of racial segregation and resource inequality on student outcomes; the role of gender, class, and race in structuring educational opportunity; the effects schooling (pre-K through college) on life course outcomes; the significance of a school's institutional environment; youth and digital innovation; and the sociology of school reform movements"--
Includes bibliographical references.
Imported from: lx2.loc.gov:210/LCDB (Do not remove)
Keywords: Utbildningssociologi; Educational sociology; Education -- Social aspects; Utbildning -- sociala aspekter; Educational sociology